Exploring information superiority : a methodology for measuring the quality of information and its impact on shared awareness - Perry, Walt L. (RAND, 2004)
Assessing how technology contributes to information superiority and decision dominance a major challenge, in part because it demands quantitative measures for what are usually considered qualitative concepts. The authors have developed a mathematical framework to aid these efforts. Additional work, such as data fitting, experimentation, linking decisions and actions, historical analysis, and gaming will further advance knowledge in this area.